2019
DOI: 10.1111/adb.12822
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in oral oxycodone self‐administration and stress‐primed reinstatement in rats

Abstract: The opioid epidemic has become a severe public health problem, with approximately 130 opioid-induced deaths occurring each day in the United States. Prescription opioids are responsible for approximately 40% of these deaths. Oxycodone is one of the most commonly abused prescription opioids, but despite its prevalent misuse, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 55 publications
6
38
0
Order By: Relevance
“…Under fixed‐ratio schedules, female rats respond more for opioids than males (Carroll, Campbell, & Heideman, 2001; Cicero, Aylward, & Meyer, 2003; Mavrikaki, Pravetoni, Page, Potter, & Chartoff, 2017). Studies using oral or vapor delivery of opioids have also observed greater consumption among female rodents (Klein, 2001; Fulenwider, Nennig, Hafeez, et al., 2019; Moussawi et al., 2020), though others have not observed a difference (Monroe & Radke, 2020). In addition, female rats and mice have been shown to maintain self‐administration at higher levels than males for drugs such as cocaine (Lynch & Carroll, 1999), methamphetamine (Roth & Carroll, 2004), and EtOH (Sneddon et al., 2020).…”
Section: Female Vulnerability In Drug Self‐administration Studiesmentioning
confidence: 99%
“…Under fixed‐ratio schedules, female rats respond more for opioids than males (Carroll, Campbell, & Heideman, 2001; Cicero, Aylward, & Meyer, 2003; Mavrikaki, Pravetoni, Page, Potter, & Chartoff, 2017). Studies using oral or vapor delivery of opioids have also observed greater consumption among female rodents (Klein, 2001; Fulenwider, Nennig, Hafeez, et al., 2019; Moussawi et al., 2020), though others have not observed a difference (Monroe & Radke, 2020). In addition, female rats and mice have been shown to maintain self‐administration at higher levels than males for drugs such as cocaine (Lynch & Carroll, 1999), methamphetamine (Roth & Carroll, 2004), and EtOH (Sneddon et al., 2020).…”
Section: Female Vulnerability In Drug Self‐administration Studiesmentioning
confidence: 99%
“…In a study investigating non–addiction-related reinforcement processes, female mice were biased toward negative reinforcement relative to positive reinforcement, in which females responded more to avoid an aversive shock than to receive a sucrose reward and were more sensitive to punishment than males ( 70 ). Female rodents more rapidly acquired morphine and heroin self-administration ( 22 , 71 , 72 ), self-administered more intravenous heroin ( 22 ) and fentanyl vapor ( 23 ) in long-access self-administration sessions, consumed more oral oxycodone during self-administration ( 73 , 74 ), and had higher motivation for fentanyl ( 75 ) than males. However, females showed no difference from males in stress-induced ( 73 ) or cue-induced reinstatement for oral oxycodone ( 74 ).…”
Section: Cues Associated With Negative Reinforcement Learningmentioning
confidence: 99%
“…Female rodents more rapidly acquired morphine and heroin self-administration ( 22 , 71 , 72 ), self-administered more intravenous heroin ( 22 ) and fentanyl vapor ( 23 ) in long-access self-administration sessions, consumed more oral oxycodone during self-administration ( 73 , 74 ), and had higher motivation for fentanyl ( 75 ) than males. However, females showed no difference from males in stress-induced ( 73 ) or cue-induced reinstatement for oral oxycodone ( 74 ). Opioid-dependent female mice also exhibited similar somatic signs of naloxone-precipitated heroin withdrawal to dependent male mice ( 22 ).…”
Section: Cues Associated With Negative Reinforcement Learningmentioning
confidence: 99%
“…In 2017 in the United States, more than 10 million people reported prescription opioid misuse [1]. Despite its importance, modeling prescription opioid abuse in rodents has been challenging [25]. Certain aspects unique to prescription opioid use, such as route of administration and pattern of intake, may contribute to abuse liability and propensity toward relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Second, prescription opioids are most commonly self-administered in a familiar setting such as the home (see Caprioli et al (2007) for a review [22]). Yet, where oral self-administration has been reported [24], experimental paradigms have required self-administration to take place in a novel context (e.g., operant chamber) and under food restriction. Environmental context (i.e., setting of drug taking) plays an important role in both drug taking and reinstatement, a finding that has been well-documented in humans and recapitulated by animal models [2227].…”
Section: Introductionmentioning
confidence: 99%